ANALISIS POTENSI DAN PENGARUH WAKTU PENYIMPANAN BUAH TERHADAP MUTU MINYAK KELAPA SAWIT TIPE DURA, PISIFERA, DAN TENERA DI KEBUN BANGUN BANDAR, DOLOK MASIHUL, SUMATERA UTARA - Nofrizal Amri; Mohammad Basyuni; Lollie AP Putri (Peronema Forestry Science Journal, 2015)
Indonesia is currently the largest producer palm oil in the world with its production about 33.000.000 ton/year in 2014. This research is dealing with potency and quality of palm oil types of dura, pisifera and tenera based on time storage of fruit (0, 7, 14, 21, 28 days). The research was performed on August to December 2014, in Bangun Bandar plantation, Dolok Masihul, North Sumatera. Parameters measured for oil potency was crude palm oil (CPO) content and for quality of palm oil were β-carotene content, deterioration of bleachability index (DOBI),  free fatty acid content, and moisture content β-carotene content and DOBI were analyzed by Spectrophotometer at 446 nm and 269 nm. Free fatty acid was determined by titration, and moisture content was measured by an electronic moisture analyzer.  Results showed that potency of palm oil types of dura, pisifera, tenera were 23,5 %, 26,2 %, 23,6 %, respectively. β-carotene content and DOBI of palm oil types of dura, pisifera, and tenera were decreased by time storage of fruit. Free fatty acid and moisture content of palm oil types of dura, pisifera, and tenera were increased by time storage of fruit. Based on the results, time of storage of fruit affected poorly in quality of palm oil. Keywords: palm oil, quality, potency, type of oil palm.